Comprehensive examination of the peer review process in academic medicine: Towards reaching unbiased decisions – Editorial. (April 2021) - Fanfan, Dino; McKenney, Mark; Elkbuli, Adel
Highlights: The implementation of double- or triple-blind review practices will ensure that authors with worthwhile and prominent research will have fair and equitable review regardless of their prominence in the field. Improving the quality of our reviews and raising the standings of our publishing authors. This makes way for healthy competition and a drive to produce high quality research. It is our responsibility to limit or eliminate bias by promoting impartiality and increasing the level of transparency between the editorial teams and authors, allowing peer review to be more inclusive, instructional, and equitable.